Development Of Interactive Multimedia Based Learning Media Using Youtube On Sunnah Prayer Materials In SDIT Al-Izzah Kotabaru South Kalimantan - Ummu Khumairah Husin Lubis; Nurmawati Nurmawati (International Journal Of Education, Social Studies, And Management (IJESSM), 2022)
The purpose of this development research is to find out the development of Interactive Multimedia-Based Learning Media using YouTube in learning the Sunnah Prayer material at SDIT Al-Izzah Kotabaru, South Kalimantan. To find out the results of students' religious learning with the Sunnah Prayer material at SDIT Al-Izzah Kotabaru, the development model used is ADDIE which has 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation (Evaluation). The subjects of this study were students of SDIT Al-Izzah Kotabaru class V. The feasibility of learning media refers to the results of media assessments by experts on the developed learning media. Interactive Multimedia-based religious learning media using YouTube on the Sunnah Prayer material developed has met the appropriate/valid criteria for use for fifth-grade SDIT students. The results of the media assessment by the validator I obtained a score of 95.4 with the "Very Valid" eligibility criteria. The results of the material assessment by validator II obtained a value of 87.5 with the "Very Valid" eligibility criteria. The results of the RPP assessment by validator I obtained a value of 92.5 with the criteria of "Very Good" and validator II obtained a value of 87.5 with the criteria of "Very Good". The results of the analysis of the effectiveness of learning media are seen from the average student learning outcomes, namely 91.8 with the criteria of 'Very Good. While the results of the analysis of the effectiveness of learning media are seen from the percentage of students' completeness, namely 86.3 with the criteria of "Very Good".